2008
DOI: 10.1007/bf03349255
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone therapy improves exercise capacity in adult patients with Prader-Willi syndrome

Abstract: Our findings seem to support the view that GH therapy has beneficial effects on physical activity and agility as well as on body composition of adult patients with PWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 50 publications
8
46
2
Order By: Relevance
“…Our randomized placebo controlled study (n = 46) found reductions in visceral fat and subcutaneous abdominal fat of nearly 25% and 20%, respectively, as measured by CT subcutaneous thigh fat was reduced by 12%, and thigh muscle volume increased by 6% [17]. Marzullo et al [24] found similar effects on visceral and subcutaneous fat in an openlabeled study (n = 13) and changes in total body composition as measured by DXA has also been reported by Mogul et al (n = 38) [16], and Gondoni et al (n = 12) [14]. Thus, all studies report an increase in lean body mass ranging from 2.2 kg to 3.3 kg and a decrease in total body fat ranging from 2.5% to 6%.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our randomized placebo controlled study (n = 46) found reductions in visceral fat and subcutaneous abdominal fat of nearly 25% and 20%, respectively, as measured by CT subcutaneous thigh fat was reduced by 12%, and thigh muscle volume increased by 6% [17]. Marzullo et al [24] found similar effects on visceral and subcutaneous fat in an openlabeled study (n = 13) and changes in total body composition as measured by DXA has also been reported by Mogul et al (n = 38) [16], and Gondoni et al (n = 12) [14]. Thus, all studies report an increase in lean body mass ranging from 2.2 kg to 3.3 kg and a decrease in total body fat ranging from 2.5% to 6%.…”
Section: Discussionsupporting
confidence: 70%
“…Short term (up to one year) controlled studies with GH treatment of adult PWS patients have demonstrated beneficial effects on body composition [14][15][16][17]. Additionally, positive effects on physical performance have been demonstrated in both children [13] and in adults [14].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, it was reported that GH therapy exerts beneficial effects on physical activity and agility as well as on body composition in adult patients with PWS (29).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in exercise capacity in response to rhGH therapy were examined in two studies 17,21) . Sode-Carlsen et al 17) performed a 10-metre walk test and found improvement (faster walking) in 6/18 rhGH-treated patients, but also in 2/16 control patients, and a repeat standing test in which 6/18 rhGH-treated and 4/16 controls had poorer scores compared with baseline.…”
Section: ) Exercise Capacitymentioning
confidence: 99%
“…Sode-Carlsen et al 17) performed a 10-metre walk test and found improvement (faster walking) in 6/18 rhGH-treated patients, but also in 2/16 control patients, and a repeat standing test in which 6/18 rhGH-treated and 4/16 controls had poorer scores compared with baseline. Gondoni et al 21) used treadmill exercise testing and reported an increase of 19% in exercise capacity (in metabolic equivalents) after 12 months of rhGH treatment (P<0.001).…”
Section: ) Exercise Capacitymentioning
confidence: 99%